Dextran Sulfate Polymer Wafer Promotes Corneal Wound Healing - Remya Ammassam Veettil; Daniela C. Marcano; Xiaoyong Yuan; Mahira Zaheer; Aparna Adumbumkulath; Richard Lee; Lucas C. Isenhart; Nicole Soriano; Kirti Mhatre; Robiya Joseph; Sendurai A. Mani; Crystal S. Shin; et al. (MDPI AG, 2021)
Eye injuries due to corneal abrasions, chemical spills, penetrating wounds, and microbial infections cause corneal scarring and opacification that result in impaired vision or blindness. However, presently available eye drop formulations of anti-inflammatory and antibiotic drugs are not effective due to their rapid clearance from the ocular surface or due to drug-related side effects such as cataract formation or increased intraocular pressure. In this article, we presented the development of a dextran sulfate-based polymer wafer (DS-wafer) for the effective modulation of inflammation and fibrosis and demonstrated its efficacy in two corneal injury models: corneal abrasion mouse model and alkali induced ocular burn mouse model. The DS-wafers were fabricated by the electrospinning method. We assessed the efficacy of the DS-wafer by light microscopy, qPCR, confocal fluorescence imaging, and histopathological analysis. These studies demonstrated that the DS-wafer treatment is significantly effective in modulating corneal inflammation and fibrosis and inhibited corneal scarring and opacification compared to the unsulfated dextran-wafer treated and untreated corneas. Furthermore, these studies have demonstrated the efficacy of dextran sulfate as an anti-inflammatory and antifibrotic polymer therapeutic.